Validasi Metode Penetapan Kadar Boraks pada Kerupuk Puli Menggunakan Spektrofotometer UV-Vis: Validation of Methods of Borax Concentrations Determination in Puli Crackers Using a UV-Vis Spectrophotometer - Oppie Anngela; Afidatul Muadifah; Dhanang Prawira Nugraha (Jurnal Sains dan Kesehatan, 2021)
Rice cracker or known as Krupuk puli is the kind of deep-fried crackers in Indonesia that made of rice seasoned with spices and flavor enhancer. Most Rice cracker sellers that peddle their products in the Ngunut traditional market, so that the sellers have to make or prepare the rice cracker as well as possible to make the cracker can be sold. In this case, most manufacturers add hazardous materials (borax) in the process of making rice crackers. The purpose of this research is to validate the method and to know the borax level of rice crackers sold in the Ngunut traditional market by using the UV-Vis spectrophotometry method. Optimization of borax wavelength in the wavelength range of 500-600 nm. The prepared samples are analyzed using UV-Vis spectrophotometry at the maximum wavelength that is 506 nm. The next step, is, validation methods, including linieritas test, accuracy test, precision test, and LOD test & LOQ. The result of this study obtained the optimum wavelength is 506 nm. Based on the validation methods that have been done, obtained the results of inference linearity in the concentration range of 5ppm; 20ppm; 35ppm; 50ppm; 65ppm with a physical value of R2 correlation of 0.993,%recovery by 96.5%, the precision value obtained by 0.375%, and the LOD value of 48.565 ppm amounting and a Loq value of 161.381 ppm. The borax level in sample A amounted to 1,380 ± 1.824 ppm, sample B of 852.1 ± 2.367 ppm, sample C of 1,373 ± 1.824 ppm, and sample D of 185.9 ± 1.788 ppm.